Analisis Pelatihan dan Pengembangan Sumber Daya Manusia (Study Kasus: PT. BTPN Tbk Kantor Cabang Jambi) - Mustika Mustika; Indri Apriani (Ekonomis: Journal of Economics and Business, 2021)
The purposes of this study are 1) To find out the types of training and HR development carried out at Bank BTPN tbk Jambi Branch Office, 2) To find out the constraints and solutions for HR training and development carried out at Bank BTPN tbk Jambi Branch Office, 3 ) To know the Strategy of Training and Human Resources Development at Bank BTPN tbk Jambi Branch Office. This study took place at Bank BTPN tbk Jambi Branch Office, the data obtained directly from books or other information in the form of interviews and documentation. The data collection method was obtained by direct observation at the Human Resources section at PT. Bank BTPN Jambi Branch Office. This study uses a qualitative descriptive method that is "done by compiling the data that has been collected then making a classification and setting standards and the position of the elements with one another so that they can be analyzed and interpreted". The results obtained from the research that the researchers conducted were employee training and development, which is a method or way to improve the quality of employees so that employee performance can increase. This Training and Development provides motivation, knowledge and improves the ability of good employees.